Mother and Child Hospital in Regional Special Hospitals of Pertiwi, South Sulawesi Province: The Importance of Individual and Customer Value in Services Utilization Decision Making (RSIA) Branch 1 of the Sitti Khadijah Muhamadiyyah in Makassar - Besse Sitti Hajar; Syahrir A. Pasinringi; Indahwaty Sidin; M. Alimin Maidin; Rachmat Latief; Hasnawati Amqam (Journal of Community Health Provision, 2022)
By comparing the levels of patient satisfaction at the Regional Special Hospitals (RSKD) for Mother and Children (Pertiwi) and the Mother and Child Hospital (RSIA), the purpose of this study is to investigate the connection between personal value and customer value (Sitti Khadijah 1 Muhammadiyah). In the present investigation, a quantitative observational study has been carried out by employing a cross-sectional design. Patients who were seeking general obstetric treatment at RSKD Ibu and Anak Pertiwi and RSIA Sitti Khadijah 1 Muhammadiyah BranchMakassar were recruited for the purpose of providing samples for this study. The findings of this study provide support to the hypothesis that an individual's own values and those of their potential patients interact significantly while making a decision about which hospital to utilize. When it comes to selecting a hospital, an individual's and a customer's personal values play a crucial influence in the decision-making process. According to the findings of research conducted on the aftereffects of RSKD, mothers and their children in the homeland place a high significance on living a quiet life as an essential component of personal value. Students' social position is given a significant amount of importance at the RSIA St. Khadijah 1 Muhammadiyah Branch in Makassar. The worth of the customer is put first in RSKD mother and child, although price based on behavior is considered to be the most important factor. It has been requested of the management at the Makassar locations of RSKD Ibu and Anak Pertiwi and RSIA St. Khadijah 1 Muhammadiyah that they conduct regular analyses of the priorities of their staff as well as their customers in order to enhance the quality of the services provided by making them friendlier and more accommodating.